A survey on the applications of machine learning in wireless sensor networks. (11th March 2021) - Chouhan, Lokesh; Chauhan, Nancy; Mahapatra, Amitosh Swain; Agarwal, Vidushi
With the dawn of the 21st century and the growth of fast, always available and low power networks, wireless sensor networks are being implemented in diverse use-cases. Wireless sensor networks are being deployed to observe, explore and control the physical world. Wireless sensor networks are generally deployed in dynamic environments. Sensor networks utilise machine learning techniques to avoid the unnecessary redesign of a wireless sensor network deployment for adapting to changing requirements. Machine learning is also used to maximise the security, efficiency, lifetime, and resource utilisation in such networks. In this paper, we present an extensive literature survey of various machine learning applications that are used or are in research to address the operational and non-operational challenges in wireless sensor networks.